2004
DOI: 10.1242/jeb.00975
|View full text |Cite
|
Sign up to set email alerts
|

Force development, energy state and ATP production of cardiac muscle from turtles and trout during normoxia and severe hypoxia

Abstract: SUMMARYThe effects of hypoxia on energy economy of cardiac muscle were compared between the hypoxia-tolerant freshwater turtle at 20°C and the hypoxia-sensitive rainbow trout at 15°C. Isolated ventricular preparations were left either at rest or stimulated at 30 min-1 to develop isometric twitch force. Under oxygenated conditions, twitch force and oxygen consumption were similar for the two species. Overall metabolism was reduced during severe hypoxia in both resting and stimulated preparations and under these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
4
19
1
Order By: Relevance
“…Shi et al, 1999;Jackson, 2002). Accordingly, heart muscle from turtles (Trachemys scripta and Chrysemys picta) shows an excellent maintenance of contractility and energy state when subjected to severe hypoxia (Overgaard and Gesser, 2004;Overgaard et al, 2007). The finding that hypoxia, compared with full oxygenation, increased twitch force development relative to the energy liberated, as assessed by O 2 consumption and lactate production (Overgaard and Gesser, 2004), is of particular interest in the present study as NO may contribute to this process.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Shi et al, 1999;Jackson, 2002). Accordingly, heart muscle from turtles (Trachemys scripta and Chrysemys picta) shows an excellent maintenance of contractility and energy state when subjected to severe hypoxia (Overgaard and Gesser, 2004;Overgaard et al, 2007). The finding that hypoxia, compared with full oxygenation, increased twitch force development relative to the energy liberated, as assessed by O 2 consumption and lactate production (Overgaard and Gesser, 2004), is of particular interest in the present study as NO may contribute to this process.…”
Section: Introductionmentioning
confidence: 80%
“…Accordingly, heart muscle from turtles (Trachemys scripta and Chrysemys picta) shows an excellent maintenance of contractility and energy state when subjected to severe hypoxia (Overgaard and Gesser, 2004;Overgaard et al, 2007). The finding that hypoxia, compared with full oxygenation, increased twitch force development relative to the energy liberated, as assessed by O 2 consumption and lactate production (Overgaard and Gesser, 2004), is of particular interest in the present study as NO may contribute to this process. For these reasons, we examined the influence of NO on mechanical performance, recorded as twitch force and resting tension, and also on cellular energy liberation, in terms of O 2 consumption and lactate production, in turtle ventricular muscle under exposure to full oxygenation and hypoxia.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A study in 2004 examined the effects of hypoxia on cellular energy state in cardiac muscle extracts in the hypoxia tolerant freshwater turtle and the hypoxia sensitive rainbow trout. These authors reported decreases in PP of 94% and 57% in the trout and turtle respectively during a period of severe hypoxia (Overgaard and Gesser, 2004).…”
Section: Adenylate Energy Charge and Phosphorylation Potentialmentioning
confidence: 94%
“…However, adenlyate ratios such as adenylate energy charge (AEC), and phosphorylation potential (PP) have been shown to be better indicators of cellular energy status (LeBras, 1995;Li et aI., 2005;Overgaard and Gesser, 2004). AEC is an indicator of the degree of phosphorylation of the ATP-ADP-AMP system, and is calculated from the following ratio:…”
Section: Using Adenylate Nucleotides As Measures Of Energy Usementioning
confidence: 99%